ASUHAN KEPERAWATAN PADA NY. V DALAM PEMBERIAN EDUKASI PIJAT OKETANI TERHADAP PENINGKATAN PRODUKSI ASI IBU POST SECTIO CAESAREA DIRUANG OBSTETRI RSUP Dr. KARIADI SEMARANG - Larasati, Andini; Wulaningsih, Indah (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Background: Sectio cesarea comes from the Latin word "Caedere" which means to cut. Sectio cesarean is a way to deliver a fetus, by making an incision in the uterine wall through the front wall of the abdomen or vagina. Sectio cesarea or caesarean birth is giving birth to a fetus through an incision in the abdominal wall (laparotomy) and uterine wall (hysterectomy). This definition does not include delivery of the fetus from the abdominal cavity in cases of uterine rupture or abdominal pregnancy (Maryunani, 2014). Sectio Caesarea is a method of delivery through an incision in the mother's uterine wall to remove the fetus provided that the uterine wall is intact and the fetus weighs more than 500 grams (Lubis, 2018). . Objective: describes the application of oketani massage to increase breast milk production. Method: using descriptive methods by describing nursing care for mothers post caesarean section to increase breast milk production. The research was conducted on January 14 2024. Results: After conducting educational intervention on the application of Oketani massage, the results can increase breast milk production. Suggestion: It is hoped that Oketano massage can be used as an independent nursing intervention to increase breast milk production.